Influence of sample return time and ambient temperature on the performance of an immunochemical faecal occult blood test with a new buffer for colorectal cancer screening. Issue 2 (March 2016) - Dancourt, Vincent; Hamza, Samia; Manfredi, Sylvain; Drouillard, Antoine; Bidan, Jeanne-Marie; Faivre, Jean; Lepage, Come
Abstract : The haemoglobin concentration measured by faecal immunochemical tests (FIT) may be decreased in cases of delayed sample return or high temperature. It is an issue of great importance. The aim of this study was to investigate the effects of sample return time and of season on the performance of an FIT (FOB-Gold) with a new buffer. The study included 20 371 participants involved in the French organized colorectal cancer (CRC) screening programme. The probability of a positive screening test, detection rates and positive predictive values for CRC and advanced adenoma were analysed according to sample return time and season of screening. A sample of positive FIT was stored for 7 days in an incubator at 20°C or 30°C. The positivity rate was 4.1% for a sample return time of up to 3 days, 4.1% for 4–5 days and 4.6% for 6–7 days ( P =0.25). In multivariate analysis, there was no association between positivity rates, detection rates and positive predictive values for CRC and advanced adenoma and the sample return time or the season of screening. At a constant temperature of 20°C, there was a decrease in the haemoglobin concentration of 5.1% after 7 days. The decrease reached 20.5% at a temperature of 30°C. It was only 4.5% during the first 4 days of storage in the incubator. With the new buffer, delay in sample return or season did not affect the clinical outcome. When temperatures reach 30°C, the faecal sample must be returned promptly.